Linking Decision-Making in Business Management in Industry 4.0 - Martin HOLUBČÍK; Gabriel KOMAN (Communications of International Proceedings, 2021)
The most important goal of industry 4.0 is to help companies meet the challenges of market variability, globalization and the shortening life cycle of the products for which it provides solutions. At present, it is the development of technology and the amount of data that is generated by almost every industry affected. Data collection and evaluation are the basic starting point for properly understanding and setting up the technologies involved in Industry 4.0. Data has become one of the most company's valuable resources and will need to be properly applied to management decisions. This concept is a broad concept, the development of which in the future is difficult to predict exactly. The aim of this article is to point out the importance of relevant and up-to-date information is a necessary starting point for decision-making in companies that need to effectively adapt strategies and make as few mistakes as possible in order to remain competitive.
Keywords: Management; Decision-making. Industry 4.0; Business; Strategy